Polycyclic High-Density Cage Compounds via Cross Metathesis - Kotha, Sambasivarao; Chaurasia, Usha Nandan (Synthesis, 2023)
The synthesis of various highly functionalized caged systems suitable as high energy density materials, which were assembled by utilization of an olefin cross-metathesis strategy, is reported. E-Selectivity was observed during the cross-metathesis by using Grubbs second generation catalyst (G-II) and N-tolyl Grubbs catalyst in most of the cross-metathesis products. The stereochemistry of the olefin formed during the cross-metathesis has been determined unambiguously by a single-crystal X-ray diffraction study.
Keywords: Cookson’s dione; Grignard addition; cross metathesis; cycloaddition; HEDMs